UPAYA PENCEGAHAN KEJAHATAN CYBERBULLYING PADA REMAJA MELALUI PLATFORM INSTAGRAM: STUDI KASUS DI SMKN X JAKARTA - Aenul Farodisa; Intan Khoirunnisa; Putri marcellina; Rania Yasmine Fadli; Dinda najwa mutiara rizqy; Eunike Angelica sarambe (Jurnal Riset Multidisiplin Edukasi, 2025)
The development of digital technology has led to the widespread use of social media among teenagers, but it also presents various risks, including cyberbullying. This study aims to examine crime prevention efforts against cyberbullying among adolescents through the Instagram platform, using a case study at SMKN X Jakarta. The research applied a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation, and analyzed thematically. The findings reveal that cyberbullying practices at the school are largely influenced by deviant traditions, such as the "odd-even" system between school cohorts, as well as weak social supervision and limited legal awareness. The types of cyberbullying identified include flaming, denigration, outing, exclusion, and masquerade. The proposed prevention efforts refer to Social Crime Prevention strategies, emphasizing the importance of character education, strengthening social bonds, and creating an inclusive and supportive school environment. This approach is expected to minimize the risk of cyberbullying by fostering empathy, commitment to norms, and teenagers’ active participation in positive activities. The study provides recommendations for schools and families to collaborate in building a safe and healthy digital culture for adolescents.